Remittances and economic growth: What lessons for the CEMAC zone? - Louis Bernard Tchekoumi; Patrick Danel Nya (Cogent Economics & Finance, 2023)
To the question of what lessons can be drawn from the relationship between migrant remittances and economic growth, this article provides an answer based on econometric evidence, using data from a sample of six countries belonging to the CEMAC zone, over the period 1990-2018. Using the PSTR2 and GMM3 models, we obtain two main results. First, there is a non-linear relationship between migrant remittances and economic growth that translates into the existence of two regimes, thus, confirming the existence of a threshold effect. Second, under the first regime, remittances have a positive and significant impact on economic growth, while under the second regime this impact is negative. The results suggest that the non-linear relationship between remittances and economic growth depends mainly on trade openness, private investment and political stability.
Keywords: C33; F24; F43; 330; economic growth; PSTR model; Remittances